Pengaruh Model Pembelajaran Snowball Throwing terhadap Kemampuan Mengidentifikasi Unsur Intrinsik Teks Drama Siswa Kelas VIII SMP Negeri O Mangunharjo - Melia Melia; M. Syahrun Effendi (LP4MK STKIP PGRI Lubuklinggau, 2019)
The purpose of this study was to determine whether there is a significant influence on the use of the snowball throwing learning model on the ability to identify the intrinsic elements of drama texts of class VII students of SMP Negeri O Mangunharjo. The research method used a pure experimental method with a control group pre-test-post-test design. The population in this study were all students of Class VIII of SMP Negeri O Mangunharjo, amounting to 148 students. Two classes were taken as a sample using simple random sampling technique, namely class VIII C totaling 30 students as the experimental class and class VIII B totaling 30 students as the control class. Data collection techniques use test techniques in the form of essay tests. This data analysis technique is carried out using the